The Evaluation of the Impact of Macroeconomic Indicators on the Performance of Listed Real Estate Companies and Reits - Cohen, Viktorija; Burinskas, Arūnas (Ekonomika, 2020)
Using quarterly data from 2006:Q1 to 2019:Q3 (55 observations), this paper examines 18 Eurozone macroeconomic variables that represent monetary policy, external and construction sectors’ performance, economic growth, investment, households’ earnings, inflation and assesses their impact on the performance of the European listed real estate companies and REITs. Empirical results demonstrate that the European listed real estate market is strongly influenced by the supply side: the construction sector and the inflation of producers’ prices; while the demand side is strongly affected by the expansionary monetary policy of ECB. Furthermore, some primary findings propose that US expansionary monetary policy shocks have an effect on the European listed real estate market. This conclusion demands further thorough research.